(untitled) (Circe de clásicos y modernos, 2018)
As a continuation of the Greek text and translation of Exagogé by Ezequiel –published in Circe 19, within the frameork of a study on the evolution of the tragic genre from the fourth century to the Byzantine period–, we present here the commentary on the text, which highlight the features that make it belong to the genre and its value as precedent of another Byzantine pieces.